It’s effective to set down systems with frequency – controlled by electrical accessories - Ustimenko, D. V.; Nikitenko, A. V. (Science and Transport Progress, 2011)
In the article the basic attention is paid to comparison of power losses in drives of pumps with various kinds of control. The resulted material focuses in determination of those units of the drive systems where the application of a frequency control is the most advantageous.